2011
DOI: 10.7224/1537-2073-13.4.163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Meditation on Pain and Quality of Life in Multiple Sclerosis and Peripheral Neuropathy

Abstract: The objective of this study was to determine whether meditation affects pain and quality of life in people with multiple sclerosis (MS) and peripheral neuropathy (PN). A total of 22 patients (10 with MS, 12 with PN) participated in a weekly meditation class over a 2-month period. A total of 18 controls (7 with MS, 11 with PN) received standard care. Primary outcome assessments were based on the 36-item Short Form Health Status Survey (SF-36) and a visual analogue scale (VAS) for pain at baseline and at 2 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 14 publications
7
79
1
Order By: Relevance
“…Both differences related to large effect sizes and were statistically significant at the 5% level. The effect size for post-intervention 15 was -.64, a medium to large effect, and the 3-month effects size was -.94, a large effect.…”
Section: Primary Outcomementioning
confidence: 89%
“…Both differences related to large effect sizes and were statistically significant at the 5% level. The effect size for post-intervention 15 was -.64, a medium to large effect, and the 3-month effects size was -.94, a large effect.…”
Section: Primary Outcomementioning
confidence: 89%
“…Three small trials found significant trends toward pain reduction, [19][20][21] but the results are difficult to interpret. Tavee et al 20 conducted an 8-week nonrandomized trial of group meditation training (n = 10 people with MS and 12 people with peripheral neuropathy) versus usual care (n = 7 people with MS and 11 people with peripheral neuropathy). Mean bodily pain scores improved for people with MS in the intervention group (n = 10, P = .03) and remained the same for the control group; between-group analyses were not conducted.…”
Section: Sensitivity Analysesmentioning
confidence: 96%
“…12 Mindfulness-based intervention studies have found positive effects for chronic pain in fibromyalgia, low back pain, arthritis, and a variety of somatization disorders, [14][15][16][17][18] but very few trials have been conducted in MS. Three small mindfulness-based MS trials have demonstrated significant trends toward pain reduction, yet results are difficult to interpret due to limitations in sample size and study design. [19][20][21] To explore the appropriateness of future mindfulness-based interventions targeting pain in MS, we evaluated the relationship between pain interference and trait mindfulness in 132 people with MS.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a growing number of individuals have turned to mind-body therapies-a specific exercise regimen including yoga, mediation, relaxation techniques, breath work, visual imagery, hypnotherapy, and biofeedback-to manage symptoms of MS. [27][28][29][30][31][32][33] For example, Yadav and colleagues 32 conducted a survey with 1110 patients with MS. Thirty-two percent reported both highly perceived psychological and physical benefits to using mind-body modalities, such as yoga, meditation, relaxation techniques, and breathing. In another study, Nayek et al 30 gathered data from 11,600 individuals with MS and found that 57.1% of the responding sample had used at least one form of complementary and alternative medicine (CAM), citing a general preference for alternative mind-body therapies.…”
Section: Mind-body Therapies For Msmentioning
confidence: 99%